E-quotes: Enunciative modalities analysis tool for direct reported speech in Arabic - Alrahabi, Al Moatasem (2015)
With rapidly growing Arabic online sources aimed to encourage people’s discussions concerning personal, public or social issues (news, blogs, forums…), there is a critical need in development of computational tools for the Enunciative Modalities analysis (attitude, opinion, commitment…). We present a new system that identifies and categorizes quotations in Arabic texts and proposes a strategy to determine whether a given speaker’s quotation conveys some enunciative modalities and potentially its evaluation by the enunciator. Our system enables two query types search for keywords within the “categorized” quotations: searching for keywords in the part potentially containing the reported speech source (the reporting clause) or searching for keywords in the part concerning the topic (the reported clause). The annotation is performed with a rule-based system using the reporting markers’ meaning. We applied our system to process a corpus of Arabic newspaper articles and we obtained promising results for the evaluation. © Springer International Publishing Switzerland 2015.